Penjatuhan Hukuman bagi Pelaku Liwath dalam Putusan Hakim Mahkamah Syar`Iyah - Raumizah, Raumizah; Zubaidi , Zaiyad; Umur, Azmil (STAINI Press, 2024)
Liwath (homosexuality) is an act associated with the Prophet Luth, in which a person has an emotional, romantic, sexual, or same-sex affection. In Aceh Province, this practice is regulated by Qanun Aceh Number 6 of 2014 concerning Qanun Jinayat, which stipulates a penalty of 100 lashes for liwath offenders. However, in the decision of the Banda Aceh City Syar'iyah Court regarding the liwath case No. 4/JN/2021/MS. Bna, the punishment imposed was only 80 luggings, in contrast to what is stated in the qanun. This study discusses three main issues: the occurrence of the liwath case in the decision, the judge's consideration in imposing the verdict, and the review of Islamic criminal law on this case. The research uses a normative juridical approach and found that the judge commuted the defendant's sentence because the defendant was polite, had never been convicted before, and promised not to repeat his actions.